Osteoarthritis model induced by intra-articular monosodium iodoacetate in rats knee - Morais,Sebastião Vieira de (2016)
ABSTRACT PURPOSE: To evaluate the usefulness of a knee osteoarthritis model through functional, radiological and microscopic changes of the synovial membrane. METHODS: Forty eight rats were divided randomly into two groups. The first received 0.9% saline in the joint and corresponded to the control group. The second was submitted to experimental osteoarthritis of the right knee induced by monosodium iodoacetate and corresponded to the osteoarthritis group. All animals were subjected to comparative tests of forced ambulation and joint movements, inability to articulate and tactile allodynia on day 1 post-experiment by forced ambulation (Roto-rod test), joint assessment of disability (weight bearing test) and assessment of tactile allodynia (Von Frey test). After inflammatory induction they were divided into four sub-groups corresponding to the scheduled death in 7, 14, 21 and 28 days when they were submitted to radiographic examination of the knee, arthrotomy and collection of the synovial membrane. RESULTS: The osteoarthritis group showed significant differences compared to control group on days 7 and 14 in Roto-rod, in weight bearing and Von Frey tests in all days, and in radiological evaluation. Microscopic examination of the synovial membrane showed abnormalities of inflammatory character at all stages. CONCLUSION: The osteoarthritis induced by intra-articular monosodium iodoacetate in rats knee is a good model to be used in related research, because it provides mensurable changes on joint movements, tactile allodynia, progressive radiological degeneration and microscopic inflammation of the synovial membrane, that represent markers for osteoarthritis evaluation